Assessing the cellular toxicity of peptide inhibitors of intracellular protein-protein interactions by microinjection. (1st January 2021) - Babu Reddiar, Sanjeevini; Al-Wassiti, Hareth; Pouton, Colin W.; Nowell, Cameron J.; Matthews, Macgregor A.; Rahman, Arfatur; Barlow, Nicholas; Norton, Raymond S.
Graphical abstract: Abstract: Inhibitors of protein-protein interactions can be developed through a number of technologies to provide leads that include cell-impermeable molecules. Redesign of these impermeable leads to provide cell-permeable derivatives can be challenging and costly. We hypothesised that intracellular toxicity of leads could be assessed by microinjection prior to investing in the redesign process. We demonstrate this approach for our development of inhibitors of the protein-protein interaction between inducible nitric-oxide synthase (iNOS) and SPRY domain–containing SOCS box proteins (SPSBs). We microinjected a lead molecule into AD-293 cells and were able to perform an intracellular toxicity assessment. We also investigated the intracellular distribution and localisation of injected inhibitor using a fluorescently-labelled analogue. Our findings show that a lead peptide inhibitor, CP2, had no toxicity even at intracellular concentrations four orders of magnitude higher than its K d for binding to SPSB2. This early toxicity assessment justifies further development of this cell-impermeable lead to confer cell permeability. Our investigation highlights the utility of microinjection as a tool for assessing toxicity during development of drugs targeting protein-protein interactions.